Improving motivation to change amongst individuals with eating disorders: A systematic review. Issue 9 (6th September 2018) - Denison‐Day, James; Appleton, Katherine M; Newell, Ciarán; Muir, Sarah
Abstract: Objective: People with eating disorders can have low motivation to change their eating disorder behaviors. Interventions aiming to enhance motivation to change have been increasingly advocated in their treatment. Questions remain regarding the strength of the evidence supporting the effectiveness of interventions that specifically focus on improving motivation. This review explored the evidence for improving motivation to change in eating disorders via clinical interventions. Method: Searches of the published and unpublished literature were conducted by searching databases (PubMed, PsychInfo, Web of Science) and trial registries (WHO ICTRP), and by contacting authors. Studies were included if they investigated an intervention for eating disorder patients, included a pre‐post outcome measure of motivation to change and were published in English. Risk of bias was also assessed. Results: Forty‐two studies were included in the final review. Evidence was found to support the use of interventions to improve motivation to change, though it was unclear whether motivational interventions present a more effective option than approaches that do not exclusively or specifically focus on motivation. However, motivational interventions were identified as being more effective than low intensity treatments. Risk of bias in included studies was generally high. Discussion: Motivation was found to increase across treatments in general, whether or not the focus of the intervention was on enhancing motivation. It is unclear if interventions specifically targeting motivation to change provide additional benefit over and above established treatment approaches.